2020
DOI: 10.31460/mbdd.749642
|View full text |Cite
|
Sign up to set email alerts
|

Key Audit Matters: A Perspective Based on Bibliometric Analysis

Abstract: Key audit matters (KAM), based on auditor judgment, are the most significant matters in the audit of financial statements of the current period. This study aims to determine the strategic diagram of key audit matters and to see the longitudinal evolution of KAM's after the released draft in 2013. To do that, the authors use science mapping and co-word analysis based on data generated from the Web of Science in SciMAT. Results show that the motor theme for KAM's is the "Audit Expectation Gap." Also, the "client… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The findings indicated that internal auditing quality is becoming more important in the articles in the reviewed journals. Aytaç & Gençoğlu (2020) performed scientific mapping and synonym analysis through the SciMat program with data obtained from the Web of Science database of key audit subjects. As a result of the analysis, the "Audit Expectation Gap" was the main theme, and "audited firm characteristics" was the main theme of the next period.…”
mentioning
confidence: 99%
“…The findings indicated that internal auditing quality is becoming more important in the articles in the reviewed journals. Aytaç & Gençoğlu (2020) performed scientific mapping and synonym analysis through the SciMat program with data obtained from the Web of Science database of key audit subjects. As a result of the analysis, the "Audit Expectation Gap" was the main theme, and "audited firm characteristics" was the main theme of the next period.…”
mentioning
confidence: 99%